Matters of the heart - Steel, Danielle (London : Corgi Books, 2010)
In this spellbinding blend of suspense and human drama, top photographer Hope Dunne fights to escape a mesmerizing sociopath who holds her in his thrall after she accepts a last-minute assignment to fly to London at Christmas and photograph one of the world's most celebrated writers--an Irish-American author known for novels of thrilling literary darkness.
Keywords: Irish Americans -- Fiction; Suspense fiction